2011
DOI: 10.1111/j.1468-3083.2010.03785.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of itraconazole pulses vs. continuous regimen in cutaneous sporotrichosis

Abstract: The efficacy and safety of Itraconazole pulse regimen for cutaneous sporotrichosis were similar to the continuous regimen. It is an effective and safe alternative treatment for cutaneous sporotrichosis, which can also lower the cost by decreasing the number of capsules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 21 publications
1
14
0
5
Order By: Relevance
“…The intermittent administration of itraconazole in pulses of 400 mg/day orally for 1 week has also been studied (27). A randomized controlled study comparing the safety and efficacy of an itraconazole pulse regimen to a continuous regimen for cutaneous sporotrichosis found similar results for both groups (238). Potassium iodide and itraconazole are contraindicated in pregnant women.…”
Section: Treatmentmentioning
confidence: 99%
“…The intermittent administration of itraconazole in pulses of 400 mg/day orally for 1 week has also been studied (27). A randomized controlled study comparing the safety and efficacy of an itraconazole pulse regimen to a continuous regimen for cutaneous sporotrichosis found similar results for both groups (238). Potassium iodide and itraconazole are contraindicated in pregnant women.…”
Section: Treatmentmentioning
confidence: 99%
“…Bonifaz et al [58] showed that pulse itraconazole was effective in treating cutaneous sporotrichosis. In a comparative study, Song et al [59] demonstrated similar efficacy and safety of itraconazole pulse regimen (200 mg bd for 1 week with a 3 week break) to the continuous (100 mg bd) regimen. Terbinafine 250 mg daily is equally efficacious as itraconazole 100 mg daily for cutaneous sporotrichosis [60] and has also been shown to be a well tolerated alternative in cases when itraconazole is contraindicated or resulted in significant drug interactions [61].…”
Section: Sporotrichosismentioning
confidence: 94%
“…Different drug protocols are used for the treatment of sporotrichosis and include terbinafine, potassium iodide, itraconazole, fluconazole, and the amphotericin B (Song et al, 2011). Adverse events, as vomiting and diarrhea, nausea, headache, hypersensitivity reactions, abdominal pain, and liver dysfunction, can occur (Lopez-Romero et al, 2011).…”
Section: Introductionmentioning
confidence: 99%